The Use of the Internet of Things in the Design and Construction of a Monitoring System for Hydrogenic Plants and Fish Ponds Using Thingspeak And Esp-01 - Sadi, Sumardi; Mulyati, Sri; Wijaya, Ikhsan Kurnia (Journal of Research in Construction, Communication, and Commercial, 2022)
Design a monitoring system on hydroganic plants and fish ponds based on Thingspeak using Arduino Mega and Uno with ESP-01 is a system that utilizes 4.0 technology in its monitoring process to make it easier for users who every day have busy working but want to remain productive with their hobby to plant. Thingspeak is one of the media that helps in the process of remote monitoring or IOT (Internet Of Things). The tools used in the process of making this monitoring system are electric drills, screwdrivers, solders, hole saws, and saws. The materials used are Arduino Mega, Arduino Uno, ESP-01, ultrasonic sensors, soil moisture sensors, DHT 11 sensors, servo motors, plastic crates as water reservoirs, mini water pumps and panel boxes. The method used in the creation of this thesis is the trial and study of literature from previous research. The purpose of making this tool is to help in monitoring the process from the beginning of the planting period to the harvest so as to save the maintenance time. Monitoring is assisted with Thingspeak's media server making remote monitoring easier. This design can be accessed by smartphone or PC that while connected to the internet can be used to monitor hydroganic plants and fish ponds because it is connected to Thingspeak server. So that it can be monitored in real time on your smartphone or PC by looking at the display that has been set up on the Thingspeak server. For the delivery time from the monitoring equipment to the server Thingspeak is 15 seconds so that within 60 minutes there is 240 data that can be obtained and from the server Thingspeak can be retrieved the data in the form of excel. From this data can make it easier for users to monitor their plants and fish ponds at any given time.